2020
DOI: 10.1126/sciadv.abb7944
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel single-molecule telomere length measurement with digital real-time PCR

Abstract: Telomere length is a promising biomarker for age-associated diseases and cancer, but there are still substantial challenges to routine telomere analysis in clinics because of the lack of a simple and rapid yet scalable method for measurement. We developed the single telomere absolute-length rapid (STAR) assay, a novel high-throughput digital real-time PCR approach for rapidly measuring the absolute lengths and quantities of individual telomere molecules. We show that this technique provides the accuracy and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…For instance, the metaphase Q-FISH method requires proliferating cells, and U-STELA is not efficient for determining telomeres greater than 8 kb. New approaches for TL analysis based on digital PCR [23] and long-read sequencing [24] have been proposed recently.…”
Section: Telomere Biologymentioning
confidence: 99%
“…For instance, the metaphase Q-FISH method requires proliferating cells, and U-STELA is not efficient for determining telomeres greater than 8 kb. New approaches for TL analysis based on digital PCR [23] and long-read sequencing [24] have been proposed recently.…”
Section: Telomere Biologymentioning
confidence: 99%
“…Using a terminal restriction fragment assay (TRF) in Arabidopsis , Hu et al (2015) concluded that RTEL1 loss does not result in telomere shortening whilst Recker et al (2014) showed that the telomeres might even be longer in the mutants. This apparent discrepancy could be addressed using recent high-resolution methods for telomere length measurement ( Lai et al, 2018 ; Kahl et al, 2020 ; Luo et al, 2020 ). More recently, RTEL1 was found to compensate telomere shortening in somatic cells in the absence of telomerase or replication protein A in Arabidopsis mutants ( Olivier et al, 2018 ; Aklilu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of this method is said to be 0.2kbp -320 kbp. While this assay is a definite improvement over other PCR-based assays, it only provides the average telomere length across all chromosomes and it is not possible to acquire subtelomere-linked and haplotype-resolved data (Luo et al, 2020).…”
Section: Telomere Length Measurement Techniquesmentioning
confidence: 99%